B-site modification of (Ba0.6Sr0.4)TiO3 ceramics with enhanced diffuse phase transition behavior. Issue 7 (May 2018) - Liu, Cheng; Shi, Liang; Lai, Yuanming; Li, Yuanxun; Jia, Lijun; Su, Hua; Li, Jie; Wen, Tianlong; Ling, Weiwei; Zhang, Huaiwu
Abstract: (Ba0.6 Sr0.4 )TiO3 (BST) ceramics modified with both Zr and Mn were synthesized via a traditional solid state reaction route. Pure perovskite structure and dense morphology were obtained for all specimens. An enhanced diffuse phase transition ( DPT ) behavior induced by Mn substitution was detected. We suggest that such enhanced DPT behavior was beneficial for BST practical applications due to the improved dielectric thermal stability while maintaining good dielectric performance. The impact of Mn concentration on the microstructure, dielectric properties, and DPT diffuseness was investigated.